Corporate Social Responsibility and Competitive Advantage: Overcoming the Trust Barrier - Shuili Du; C. B. Bhattacharya; Sankar Sen (European School of Management and Technology (ESMT), 2010)
This research builds on the complementary corporate social responsibility (CSR) literatures in strategy and marketing to provide insight into the efficacy of CSR as a challenger's competitive weapon against a market leader. Through an investigation of a real world CSR initiative, we show that the challenger can reap superior business returns among consumers who had participated in its CSR initiative, relative to those who were merely aware of the initiative. Specifically, participant consumers demonstrate the desired attitudinal and behavioral changes in favor of the challenger, regardless of their affective trust in the leader, whereas aware consumers' reactions become less favorable as their affective trust in the leader increases. Furthermore, participation, unlike mere awareness, transforms the nature of the consumer-challenger relationship from a transactional one to a communal, trust-based one.
urn:nbn:de:101:1-201106143706
Keywords: 650; corporate social responsibility; competitive strategy; challenger brand; affective trust; Corporate Social Responsibility; Wettbewerbsstrategie; Firmenimage; Konsumentenverhalten